Development of Nanoemulsion Based Gel Loaded with Phytoconstituents for the Treatment of Urinary Tract Infection and in Vivo Biodistribution Studies - Atinderpal Kaur; Sonal Gupta; Amit Tyagi; Rakesh Kumar Sharma; Javed Ali; Reema Gabrani; Shweta Dang (Tabriz University of Medical Sciences, 2017)
Purpose: A nanoemulsion based gel containing Polyphenon 60 (P60) and cranberry (CRB) has been developed to deliver via intravaginal route for the treatment of urinary tract infection. Methods: Polyphenon 60 and cranberry were loaded in a single nanoemulsion gel (NBG) by ultra-sonication method and characterized for particle size, rheological properties, in vitro release and growth curve analysis. P60+CRB NBG were radiolabelled using technetium pertechnetate (99mTc) to perform in vivo pharmacokinetic studies in animals. Results: The finalized NE had a droplet size of 58±1 nm. In vitro release of 90.92 ± 0.6% in 8 hr for P60 and 99.39 ± 0.5% in 6 hr for CRB was observed in simulated vaginal fluid. Growth curve of E. coli indicated the inhibitory action of nanoemulsion based gel at the fifth hour of inoculation. Gamma scintigraphy studies on female Sprague-Dawley rats showed transport of nanoemulsion based gel from the vaginal cavity into the systemic circulation. Further, biodistribution studies with radiolabelled P60+CRB NBG showed significant higher uptake of radiolabelled actives by kidney (3.20±0.16) and urinary bladder (3.64±0.29), when administered intravaginally. Conclusion: The findings suggested 99mTc-P60+CRB NBG can potentially be transported through vaginal cavity and reach the target organs and showed effective distribution in organs affected in urinary tract infection